2017
DOI: 10.1590/1984-0462/;2017;35;4;00002
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência De Genuvalgo Em Escolas Públicas Do Ensino Fundamental Na Cidade De Santos (Sp), Brasil

Abstract: Objective: To evaluate the prevalence of genu valgum and associated factors in elementary school students. Methods: Cross-sectional study, carried out in 2015, with 1,050 children and adolescents enrolled in an elementary school in Santos, Southeast Brazil. Misalignment of the knee was assessed by intermalleolar distance, considering ≥8 cm or <8 cm. Inter-examiners reliability was measured by Kappa coefficient, resulting in 0.94. Nutritional status was evaluated according to the World Health Organization 2006 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 10 publications
4
9
0
1
Order By: Relevance
“…Another Brazilian study found much higher prevalence in of over of valgus knee (56.0%), however, over 60.0% of the examined population was overweight or obese, which could have strongly affected the results [41]. In our study a statistically significant difference in the prevalence of valgus knee in normal, overweight, and obese children was observed, consistent with previous studies [25, 26]. In addition we found sex-specific differences in the prevalence of knee and heel defects, which was in contrast to findings of Walker et al [42].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Another Brazilian study found much higher prevalence in of over of valgus knee (56.0%), however, over 60.0% of the examined population was overweight or obese, which could have strongly affected the results [41]. In our study a statistically significant difference in the prevalence of valgus knee in normal, overweight, and obese children was observed, consistent with previous studies [25, 26]. In addition we found sex-specific differences in the prevalence of knee and heel defects, which was in contrast to findings of Walker et al [42].…”
Section: Discussionsupporting
confidence: 89%
“…In those available, the prevalence of valgus and varus knee varies significantly. A Brazilian study by Ciaccia et al [26] reported the 7.1% prevalence of knee valgus in children aged 7–12. Another Brazilian study found much higher prevalence in of over of valgus knee (56.0%), however, over 60.0% of the examined population was overweight or obese, which could have strongly affected the results [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RT can also be an alternative intervention method in the rehabilitation of musculoskeletal injuries affecting the knee [2]. Excessive misalignment of the patella is a very frequent type of lesion in the RT, especially in the squat exercise, which may be, among other factors, influenced by the valgus knee or dynamic varus [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Na realização de exercícios de TF, o desalinhamento excessivo da patela é um tipo de lesão muito frequente, sobretudo no exercício agachamento, que pode ser entre outros fatores, influenciado pelo joelho valgo ou varo dinâmico 4 . Os principais motivos que podem acarretar estes desvios na articulação do joelho têm sido frequentemente associados a estabilização dinâmica do joelho, que é garantida pela musculatura que circunda a articulação 5 .…”
Section: Introductionunclassified